Ion-Transfer Voltammetric Behavior of Protein Digests at Liquid|Liquid Interfaces - Herzog, G.; Roger, A.; Sheehan, D.; Arrigan, Damien (American Chemical Society, 2010)
The development of new methods for the detection of proteins and peptides is of widespread importance. In this work, the electrochemical behavior of peptide mixtures resulting from proteolytic digestion of proteins was investigated at the polarized liquid|liquid interface (or the interface between two immiscible electrolyte solutions, ITIES). The influence of pepsin digestion on three proteins (hemoglobin, lysozyme, and cytochrome c) was studied, and it was revealed that resulting cyclic voltammograms of the three protein digests were different due to the unique peptide mixtures for a given protein. Differential pulse stripping voltammetry of protein digests enabled the detection of digested proteins at concentrations ranging between 0.55 and 4.22 M. A limit of detection of 0.55 M of the initial concentration of protein was achieved, demonstrating the analytical possibilities of such an electrochemical method. These results show that ion transfer voltammetry offers the opportunity to study and develop label-free detection of peptides resulting from enzymatic digestions of proteins and may thus have a role in development of new proteomic technologies.